The political cartoons of Derso and Kelen : years of hope and despair - Slater, Stefan (Lund Humphries, 2023)
Alois Derso (1888-1964) and Emery Kelen (1896-1978) were remarkable cartoonists who became internationally renowned, particularly for their depictions in the 1920s of efforts to build a better world following the establishment of the League of Nations; of the rise of fascism in the thirties; and of the world cooperation through the United Nations that emerged in the forties. Their sequence of cartoons, imbued with humour, wit, gentle satire, artistry and vision, captures the Zeitgeist of a period of history that resonates today. Surprisingly, no comprehensive account of their work and lives has been published before. The authors analyse and discuss the extraordinary political insights revealed in the cartoons, which contribute to our understanding of those years. Drawing on original research, this overdue book delves into all aspects of Derso and Kelen's careers, including the unusual, if not unique, technical nature of their artistic collaboration and Kelen's additional gifts as a writer. It will inform the non-expert of the history of the time and the often overlooked role of cartoons as historical evidence. So memorable and informative are the images, it will also be a useful supplement to the literature on modern history, international relations and art